Nonviolence and Civil Resistance in San José de Apartadó - Rivera-García, Jose Luis (Sociedad y Economía, 2020)
San José de Apartadó is a district of the municipality of Apartadó, located in the subregion of Urabá, Colombia, 320 km from Medellín, capital of the department of Antioquia. More than 20 years ago, faced with the intensification of violence due to the armed conflict, 500 peasants declared their neutrality in front of the armed actors and were configured as a Community of Peace (CdP), claiming the right to be respected by all the armed actors. The question that arises is how is it possible that a peasant community without greater preparation in issues of Nonviolence, is able to initiate and maintain a process of nonviolent resistance to war in a scenario as hostile as that of Urabá? To answer this, Pardo, Morales and Gómez (2017), three professors from the University of Quindío, review theoretical and historical background of the nonviolent action and review some facts of the violence in Colombia, situating the struggle of the San José de Apartadó CdP as a local reference, exceptional and exemplary of resistance and civil defense.